Components Of User Education Programmes For Undergraduates In Universities - Henry, Songu; Ifere, Mimi-Patricia Eugene; Felicia, Angereke; Iyamba, Elizabeth-Amu Opinion (Eduscape : Journal of Education Insight, 2024)
This study investigates the key components of user education programs offered to undergraduate students at universities in Cross River State, Nigeria, with the goal of enhancing their academic and research skills. These programs are crucial for developing the necessary information literacy among students, and understanding their specific implementation in Cross River State is significant for fostering academic success. However, the effectiveness of these programs in meeting the students' needs has not been thoroughly evaluated. The research addresses the questions: What are the components of user education programs provided to undergraduate students at universities in Cross River State, Nigeria, and are these students satisfied with their use? This area has been under-researched due to a lack of focus on the unique educational context of this region. Using a survey research design, the study sampled 285 out of a total population of 987 third-year undergraduate students, selected through proportionate stratified random sampling using the Taro Yamane formula. Data were collected using questionnaires administered personally by the researcher with assistance from two research aides and analyzed using descriptive statistics including frequency counts and percentages. The findings indicated that the user education programs include components such as information literacy, digital literacy, research skills, library usage, and academic writing skills. Most students reported satisfaction with the programs. The study recommends enhancing these programs with more practical sessions and additional resources to improve the student learning experience.